Implementation of Fruit Grading & Sorting Station Using Digital Image Processing Techniques - Ghulame Mustafa Abro; Kundan Kumar (Sir Syed University Research Journal of Engineering and Technology)
No doubt that today's technology has approximately solved many common as well as complex issues. Engineers and researchers are always in the quest for the best, brief and efficient methods to cope up the real world problems, hence fruit grading and sorting are one of the problems in export/import industry. In this regard industry requires a station that can check the skin of fruit, i.e. an apple whether it has rotten spots on it or not beside this whole procedure this specific station will also check the radius of an apple for sorting it further for packaging process. This whole procedure will be followed by a running conveyor belt, 2 AC plungers and a wooden box in between them, which will have 5 Mega pixel camera mounted on it. The camera will be triggered by a brief algorithm of digital image processing designed on the platform of MATLAB R2015a version and conclude whether the fruit, i.e. an apple is healthy or having some rotten spots on its skin. Once results are shown, then the algorithm will activate the respective plunger for grading and sorting of apples.